2006
DOI: 10.1038/sj.onc.1209984
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide-mediated inhibition of androgen receptor activity: possible implications for prostate cancer progression

Abstract: Chronic inflammation increases the risk of cancer and many cancers, including prostate cancer, arise at sites of chronic inflammation. Inducible nitric oxide synthase (iNOS) is an enzyme dominantly expressed during inflammatory reactions. Although synthesis of high amounts of nitric oxide (NO) by iNOS has been demonstrated in pathophysiological processes, such as acute or chronic inflammation, autoimmune diseases or tumorigenesis, the role of iNOS activity in most of these diseases is poorly understood. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 47 publications
5
53
0
Order By: Relevance
“…The inhibitory effect of NO on the DNA-binding of zinc-finger proteins is most likely due to a reversible S-nitrosation of cysteine residues of the two cys4-type zinc fingers, which are essential for DNA-binding . Although NO inhibits DNA-binding activity of the nuclear steroid hormone receptors, it does not affect intracellular receptor protein levels or its nuclear import as recently shown for the AR (Cronauer et al, 2006). The nuclear localization signal of EcR located in the CD-domain is functional in the absence of zinc-fingers (Gwozdz et al, 2007), which confirms that NO does not change nuclear import.…”
Section: No As a Tool To Study Intranuclear Localization Of Nuclear Rsupporting
confidence: 60%
“…The inhibitory effect of NO on the DNA-binding of zinc-finger proteins is most likely due to a reversible S-nitrosation of cysteine residues of the two cys4-type zinc fingers, which are essential for DNA-binding . Although NO inhibits DNA-binding activity of the nuclear steroid hormone receptors, it does not affect intracellular receptor protein levels or its nuclear import as recently shown for the AR (Cronauer et al, 2006). The nuclear localization signal of EcR located in the CD-domain is functional in the absence of zinc-fingers (Gwozdz et al, 2007), which confirms that NO does not change nuclear import.…”
Section: No As a Tool To Study Intranuclear Localization Of Nuclear Rsupporting
confidence: 60%
“…AR-positive LNCaP cells were routinely transfected with the pGL3E-Probasin reporter (200 ng/well) as previously described (22). pGL4hRluc used to correct for transfection efficiency was co-transfected in every experiment (80 ng/well).…”
Section: Methodsmentioning
confidence: 99%
“…Higher levels of NO· can be produced by an inducible nitric oxide synthase (iNOS, also known as NOS2) in different cell types, but mainly in macrophages, upon infection to kill pathogens (reviewed in reference 9). The higher levels of NO· produced by iNOS have been implicated in various human inflammatory diseases and neurodegenerative diseases (reviewed in references 9 and 12) and in chronic inflammation-related tumorigenesis (18,33). Recent studies have also shown that chemical-generated higher levels of exogenous NO· can induce tumor cell apoptosis in vitro and in animal studies (37; reviewed in reference 1), raising interests in therapeutic exploration of NO·-releasing reagents as antitumor prodrugs.…”
mentioning
confidence: 99%